Variability in the Patterns of Terrestrial Mammals in Visiting The Natural Salt-Licks At a Tropical Forest - Andy R. Mojiol; Wing-Shen Lim (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2022)
Natural salt-licks are visited frequently by various species of terrestrial mammals, but the variability in environmental conditions can modify the mammalian visitation pattern in an inland tropical forest. Given that no similar research has been conducted at Segaliud-Lokan Forest Reserve in Sabah (Malaysia), a scientific research was conducted from July 2019 to February 2020 (eight months), to investigate the effects of variability in the environmental conditions on mammalian visitation patterns to the local natural salt-licks, applying the field assessment and camera trapping techniques. Over all, a total of 12 different mammal species were recorded at four selected salt-licks, and then the visitation frequencies of certain species were confirmed to be significantly influenced by the seasonal variability in rainfall patterns, and also by the variations in onsite and surrounding conditions. Further research is required to validate the influences of variability in explanatory variables that were not included in this scientific study. Kata kunci (Keywords): Environmental Condition, Natural Salt-lick, Segaliud-Lokan Forest Reserve, Terrestrial Mammals